Uncovering the structure of self-regulation through data-driven ontology discovery - Ian W. Eisenberg (Nature Portfolio, 2019)
Scientific progress relies on integrating and building on existing knowledge. Here, the authors propose improving cumulative science by developing data-driven ontologies, and they apply this approach to understanding the construct of self-regulation.